2005
DOI: 10.1091/mbc.e05-04-0350
|View full text |Cite
|
Sign up to set email alerts
|

Differential In Vivo Binding Dynamics of Somatic and Oocyte-specific Linker Histones in Oocytes and During ES Cell Nuclear Transfer

Abstract: The embryonic genome is formed by fusion of a maternal and a paternal genome. To accommodate the resulting diploid genome in the fertilized oocyte dramatic global genome reorganizations must occur. The higher order structure of chromatin in vivo is critically dependent on architectural chromatin proteins, with the family of linker histone proteins among the most critical structural determinants. Although somatic cells contain numerous linker histone variants, only one, H1FOO, is present in mouse oocytes. Upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 30 publications
4
42
0
Order By: Relevance
“…The dynamic exchange of remodeling proteins on the MMTV array are consistent with our in vitro results obtained from rapid UV laser crosslinking where purified SWI/SNF binds to and is displaced from purified MMTV chromatin (Fletcher et al, 2002;Nagaich et al, 2004). Because the FRAP recovery kinetics of chromatin proteins are directly related to their chromatinbinding properties (Lefebvre et al, 1991;Fragoso et al, 1998;Lever et al, 2000;Kimura and Cook, 2001;Hager et al, 2002;Kimura et al, 2002;Maruvada et al, 2003;Phair et al, 2004;Becker et al, 2005;Chen et al, 2005), we conclude that the remodeling proteins with the slowest exchange rate reside longest on the MMTV promoter and associate most strongly with MMTV chromatin. A comparison of the kinetic properties of chromatin-remodeling complexes revealed that BRG1 was more strongly associated with the MMTV array than BRM ( Figure 6D).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The dynamic exchange of remodeling proteins on the MMTV array are consistent with our in vitro results obtained from rapid UV laser crosslinking where purified SWI/SNF binds to and is displaced from purified MMTV chromatin (Fletcher et al, 2002;Nagaich et al, 2004). Because the FRAP recovery kinetics of chromatin proteins are directly related to their chromatinbinding properties (Lefebvre et al, 1991;Fragoso et al, 1998;Lever et al, 2000;Kimura and Cook, 2001;Hager et al, 2002;Kimura et al, 2002;Maruvada et al, 2003;Phair et al, 2004;Becker et al, 2005;Chen et al, 2005), we conclude that the remodeling proteins with the slowest exchange rate reside longest on the MMTV promoter and associate most strongly with MMTV chromatin. A comparison of the kinetic properties of chromatin-remodeling complexes revealed that BRG1 was more strongly associated with the MMTV array than BRM ( Figure 6D).…”
Section: Discussionsupporting
confidence: 87%
“…In fact, this modulation is one of the key mechanisms essential for the functional role of nuclear hormone receptors (Stenoien et al, 2001;Schaaf and Cidlowski, 2003;Stavreva et al, 2004;Elbi et al, 2004b;Farla et al, 2005;Rayasam et al, 2005). In vivo FRAP has been used to study the dynamic properties of chromatin proteins and that the FRAP recovery kinetics of chromatin proteins are directly related to their chromatin-binding properties (Lefebvre et al, 1991;Fragoso et al, 1998;Lever et al, 2000;Kimura and Cook, 2001;Kimura et al, 2002;Maruvada et al, 2003;Phair et al, 2004;Becker et al, 2005;Chen et al, 2005). Because BRG1 and BRM were selectively recruited to the MMTV array in response to hormone (Figures 2 and 3), we used FRAP to study the binding kinetics of chromatin-remodeling complexes at the amplified MMTV target in vivo.…”
Section: Chromatin-remodeling Complexes Have Distinct Kinetic Propertmentioning
confidence: 99%
“…Moreover, antibody array assays have suggested that H1foo may interact with many kinds of cell cycle-related proteins including CDC25, an activator of MPF (data not shown). Recent studies of fluorescence recovery after photobleaching (FRAP) revealed that H1foo has high mobility [10,32], potentially facilitating effective recruitment of cell cycle-related factors on chromatin. It is reasonable to speculate that H1foo has greater mobility than somatic linker histones within oocytes, which have significantly more cytosol space than somatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…In Xenopus embryos, the transition from an oocyte to a somatic type of linker histone modulates cell fate in response to a morphogen (17). In nuclear transplantation in mouse and Xenopus, a loss of somatic H1 and incorporation of oocyte linker histone have been described (18)(19)(20)(21)(22). However, it remains unclear to what extent these changes are causally connected with the transcriptional reactivation of pluripotent genes.…”
mentioning
confidence: 99%